Separating Crime from Punishment: The Constitutional Implications of United States v. Halper - Linda S. Eads (Washington University Law Quarterly, 1990)
Last Term, the Supreme Court in United States v. Halper, unanimously created a rule of law that will disrupt federal, state, and local governments' ability to enforce a vast array of important regulatory schemes, including environmental protection, securities regulation, and tax collection. This likely disruption flows from the Court's recognition that certain constitutional protections, previously thought only available to criminal defendants, are at times equally accessible to civil defendants from whom government is attempting to collect civil penalties for proscribed activity. While the Court's decision in Halper focused only on the extension of the double jeopardy clause to civil penalty proceedings, its reasoning and holding are sufficiently broad to allow the application of other constitutional protections to government-initiated civil penalty cases. These additional constitutional protections could include the eighth amendment, the self-incrimination clause of the fifth amendment, and the trial guarantees of the sixth amendment. In essence, all of the positions taken by the Halper Court lead to the overarching principle of the case: Once a court determines that awarding a civil penalty in a particular case serves the aims of retribution and deterrence, then the civil penalty as applied to that case creates the kind of punishment which triggers certain constitutional protections traditionally afforded only criminal defendants. The simplicity of this principle hides the radical points of departure it signals. This Article will discuss and analyze these points of departure in order to establish the danger the Halper doctrine poses to the orderly process of government.
Keywords: Punishment; Double jeopardy